(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
"I wanted to make a memorial that was alive, not an object or set of objects to make a pilgrimage to; a memorial that would come to you, that would appear in your city, town or shopping centre, intervening in your daily life". With these words Jeremy Deller introduces us to his We Are Here Because We Are Here, a true monument celebrating the centenary of the Battle of the Somme on 1st July 1916, in which almost twenty thousand British soldiers succumbed. In fact, with the help of Rufus Norris, director of the National Theatre, Deller organised a gigantic mass performance in which about 2000 volunteers worked, disguised as soldiers of the First World War who wandered around the main cities of the United Kingdom without anyone having warned the citizens of their presence. In my paper I will try to investigate, through Deller’s work (and through the comparison with other artistic experiences), how some contemporary artistic interventions try to exploit the mechanisms of performance in order to reconstruct historical events not only relying on the strategies of re-enactment, but also resorting to an immersive and unexpected relationship able to produce an extreme involvement. We Are Here Because We Are Here thus contributes to the reconstruction of memory not through the description of historical facts, nor even through their celebration, but through a process that solicits the emotional states to which, in the harshest moments of the war, the community is subjected.